Pre-cachexia in patients with stages I–III non-small cell lung cancer: Systemic inflammation and functional impairment without activation of skeletal muscle ubiquitin proteasome system - Op den Kamp, C.M.; Langen, R.C.; Minnaard, R.; Kelders, M.C.; Snepvangers, F.J.; Hesselink, M.K.; Dingemans, A.C.; Schols, A.M. (Lung cancer (Amsterdam, Netherlands), 2012)
Cachexia is a prevalent phenomenon of non-small cell lung cancer (NSCLC) which is responsible for increased mortality and deterioration of physical performance. Preclinical research indicates that systemic inflammation induces cachexia-related muscle wasting through muscular Nuclear Factor-kappa B (NF-κB) signaling and subsequent ubiquitin proteasome system (UPS)-mediated proteolysis. As these pathways could be a target for early intervention strategies, it needs to be elucidated whether increased activation of these pathways is already present in early stage NSCLC cachexia. The aim of the present study was therefore to assess muscular NF-κB and UPS activation in patients with NSCLC pre-cachexia. Sixteen patients with newly diagnosed stages I–III NSCLC having <10% weight loss and ten healthy controls were studied. Body composition, systemic inflammation and exercise capacity were assessed in all subjects and NF-κB and UPS activity in vastus lateralis muscle biopsies in a subset. Patients showed increased plasma levels of C-reactive protein (CRP) (P<0.001), soluble Tumor Necrosis Factor receptor 1 (sTNF-R1) (P<0.05), fibrinogen (P<0.001) and decreased levels of albumin (P<0.001). No changes in fat free body mass or skeletal muscle NF-κB and UPS activity were observed, while peak oxygen consumption (V˙O2 peak) was significantly decreased in patients compared with healthy controls. In conclusion, this exploratory study demonstrates significantly reduced exercise capacity in NSCLC pre-cachexia despite maintenance of muscle mass and unaltered indices of UPS activation. The absence of muscular NF-κB-dependent inflammatory signaling supports the notion that transition of systemic to local inflammation is required to initiate UPS-dependent muscle wasting characteristic for (experimental) cachexia.